A replicator-specific binding protein essential for site-specific initiation of DNA replication in mammalian cells - Zhang, Ya; Huang, Liang; Fu, Haiqing; Smith, Owen K.; Lin, Chii Mei; Utani, Koichi; Rao, Mishal; Reinhold, William C.; Redon, Christophe E.; Ryan, Michael; Kim, RyangGuk; You, Yang; et al. (Nature communications, 2016)
Mammalian chromosome replication starts from distinct sites; however, the principles governing initiation site selection are unclear because proteins essential for DNA replication do not exhibit sequence-specific DNA binding. Here we identify a replication-initiation determinant (RepID) protein that binds a subset of replication-initiation sites. A large fraction of RepID-binding sites share a common G-rich motif and exhibit elevated replication initiation. RepID is required for initiation of DNA replication from RepID-bound replication origins, including the origin at the human beta-globin (HBB) locus. At HBB , RepID is involved in an interaction between the replication origin (Rep-P) and the locus control region. RepID-depleted murine embryonic fibroblasts exhibit abnormal replication fork progression and fewer replication-initiation events. These observations are consistent with a model, suggesting that RepID facilitates replication initiation at a distinct group of human replication origins. Origins of mammalian DNA replication are poorly characterised because they lack an Identifiable consensus sequence. Here the authors identify RepID, a protein that binds to a subset of G-rich replication origins and facilitates initiation from those origins.